Pengenalan Dasar Pengkodingan Secara Daring pada SMK Pemda Lubuk Pakam - Anita Sindar Sinaga; Arjon Samuel Sitio; Petti Sijabat (Abdimas Universal, 2020)
The use of instructional media in the teaching and learning process is one of the efforts to improve the effectiveness and quality of the learning process which in turn can improve the quality of student learning outcomes. Media resulting from video sample technology are used as learning media so students can repeat the material shared. The quality of HR skills needs to be improved through training to face the challenges of the workforce later. Skill computing has become a trend of capability that is in demand in the digital revolution 4.0. Learning of MatLab programming is carried out by the Community Service Team to encourage the interest of students in class X of the private SMK in Lubuk Pakam regional government in programming. In addition to utilizing the MatLab variable for learning mathematics, at the end of learning, students are advised to produce a simple program.